Climate change and Pacific Island food systems - Bell, J.; Taylor M; Amos, M.; Andrew N (2016)
Climate change in Pacific Island countries and territories (PICTs) is projected to have significant impacts, including rising sea-levels, more violent tropical cyclones and droughts. Fish stocks in the tropical regions of the Pacific are expected to be directly affected by any changes that may occur in the ocean’s ecosystem. The four alternative scenarios of the future of the Pacific food systems that are reported in this booklet provide important insights into the different dimensions of the food system, including fisheries and forests, trade, affordability and consumption, and public health. The scenarios offer essential information for policy-makers, in order for them to be able to test and take steps toward developing policies that enhance resilience and strengthen adaptation to climate change among fishers and farmers in the Pacific region.